A study on the usefulness of financial reporting with reference to lending bankers / Johep Ros - Ros, Johep (1994)
This paper is an attempt to examine the usefulness of financial reporting with particular reference to banks. The stewardship function of the management in a business enterprises, is to produce the common report known as an annual report. This paper is therefore intended to highlight the objectives of financial reporting and the users of financial reporting information. In relation to this, the author also discuss on commercial banks' functions with special emphasis on lending. The research done by the author is base on commercial banks procedures in loan considerations. Though not exhaustive, the outcome shows that banks do make use of financial statement as one of the criteria in lending procedures and policies. Other than that, non-financial factors are also considered.